Controllability and Observability for Linear System - Zhou Gaofeng; Zhang Qi (Modern Control Systems: Theory, Design and Applications, 2025)
Controllability and observability were two very important conceptions in the control system, hence they were mainly narrated and demonstrated in this chapter. This chapter discussed the controllability and its judgment criterion, observability and its judgment criterion for linear systems. Then structural decomposition and the minimal realization of the transfer function matrix would also be discussed.